THE RELATIONSHIP BETWEEN VULVA HYGIENE KNOWLEDGE AND BEHAVIOR AND THE INCIDENCE OF PRURITUS VULVAE IN ADOLESCENT GIRLS AT SMK PURNAMA 1 SOUTH JAKARTA IN 2023 - Aisya Triani Fadiya; Nurfadhilah; Nur Romdhona; Hardiman SG (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
The most prevalent symptom of pruritus vulvae is the presence of itching in the female genital area, as evidenced by the fact that 5.2 million teenage girls in 17 Indonesian provinces frequently have problems that follow menstruation and are brought on by poor hygiene. The purpose of this study is to determine the correlation between the prevalence of vulva pruritus and vulva cleanliness behavior and knowledge. The study, which was carried out at SMK Purnama 1 South Jakarta, used a cross-sectional study design and a quantitative, analytical technique. A basic random sampling procedure was used to calculate the sample size, which came out to be 77 pupils. The chi-square test with α = 0.05 is used for data analysis. The findings revealed that up to 84.4% of those surveyed had pruritus vulvae. Furthermore, there was a correlation between the occurrence of vulva pruritus and knowledge (p-value = 0.007) as well as vulva cleanliness behavior (p-value = 0.003). The prevalence of vulva pruritus was significantly correlated with vulva cleanliness practice and knowledge. Additional resources, health professional advice, and consultations on reproductive health particularly vulva hygiene are required to prevent vulva pruritus in students.